Detection of intercellular adhesion genes: the virulence genes in biofilm formation of staphylococcus epidermidis / Fazlin Haron - Haron, Fazlin (2017)
Staphylococcus epidermidis (S. epidermidis) is a natural constituent of the human skin and mucosal surfaces. Nowadays, S. epidermidis are recognized as opportunistic human pathogens and are widespread in the environment. Generally, the success of S. epidermidis as a pathogen has to be attributed to its ability to adhere to surfaces and to remain there under the cover of a protection extracellular material in relative silence. The intercellular adhesion (ica) operon genes are the virulence genes of S. epidermidis that consist of icaA, icaB, icaC and icaD respectively. This study only focusing on two ica genes (icaA, icaD). Biofilm formation of S. epidermidis is mediated by the expression of the ica genes operon. Thus, this research aim to detect the intercellular adhesion (ica) genes in biofilm formation of S. epidermidis. In this study, twenty-one samples of S. epidermidis were sub-cultured from previous study samples. Several identification test were performed to identify and confirm S. epidermidis spp. from the samples. Detection of targeting icaA and icaD genes were performed by using real-time polymerase chain reaction (qPCR). Based on the result obtained, from twenty-one samples tested only five (23.8%) expressed the icaA genes. The remaining 16 (76.2 %) samples showed no genes were observed. The result for icaD genes was non-specific from twenty-one samples that performed qPCR. Among ica genes, icaA and icaD have been reported to play a significant role in biofilm formation in S. epidermidis. It is significant to note that both genes were demonstrated in biofilm producing strains of S. epidermidis although there were no icaD genes observed in this study. Further research is needed to discover more specific virulence properties of ica operon genes and gain awareness about biofilm formation that occurred not only on medical devices but also in human body.